Offshoring, Outsourcing and Production Fragmentation Linking Macroeconomic and Micro-Business Perspectives - Radlo, Mariusz-Jan.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
In this book, Radlo increases understanding of offshoring, outsourcing and international production fragmentation, and explains the impact of this phenomenon on the economies and enterprises. Key features include a comprehensive theoretical explanation of offshoring and outsourcing at both macroeconomic and microeconomic level, as well as an explanation of practical consequences of the mentioned phenomenon for the development of the global economy, national economies, concrete industries and enterprises. Unlike other publications, which are often characterized by narrow management or a macroeconomic approach to the analysis of offshoring and outsourcing, Radlo's text offers real insight into the global impact of production fragmentation.
Keywords: Industrial organization; Industries; Organization; Macroeconomics/Monetary Economics//Financial Economics; Political Economy/Economic Systems